1973
DOI: 10.1029/jc078i033p07884
|View full text |Cite
|
Sign up to set email alerts
|

Is the west Antarctic Ice Sheet disintegrating?

Abstract: Data pertaining to the dynamics and history of the west antarctic ice cover are reviewed and interpreted in terms of a possible inherent instability of the ice cover. A study of published data concerning the past and present ice cover of West Antarctica indicates that during the last few million years the ice sheet has been retreating in stages, each retreat stage being preceded by an advance of comparable duration. Thus disintegration of the west antarctic ice sheet seems to follow the disintegration pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(170 citation statements)
references
References 51 publications
5
164
0
1
Order By: Relevance
“…39° E. It is concluded that the ice sheet was shrinking along a part of the chain during this observation period, as estimated using a similar method in the West Antarctic ice sheet (Hughes, 1973;Whillans, 1973;Thomas, 1976). However, surface lowering was not necessarily · taking place over the entire area of Mizuho Plateau.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…39° E. It is concluded that the ice sheet was shrinking along a part of the chain during this observation period, as estimated using a similar method in the West Antarctic ice sheet (Hughes, 1973;Whillans, 1973;Thomas, 1976). However, surface lowering was not necessarily · taking place over the entire area of Mizuho Plateau.…”
Section: Discussionmentioning
confidence: 96%
“…Using their data, Nye ( 1975) discussed the resultant lowering of the ice-sheet surface. Meanwhile, it was suggested that the West An tarctic ice sheet is currently thinning (Hughes, 1973;Weertman, 1976 ;Thomas, 1976) and is slightly thinning or stable (Whillans, 1973(Whillans, , 1976(Whillans, , 1977. Thomas ( 1976) estimated that the Ross Ice Shelf is growing thicker by almost I m a-I in the vicinity of its grounding line.…”
mentioning
confidence: 99%
“…There is considerable disagreement concerning the current state of equilibrium of the West Antarctic ice sheet. Hughes ( 1975) suggested that the ice sheet may be collapsing, and measurements of surface strain-rate that were made near the ice-sheet summit have been interpreted as indicating thinning of perhaps a few centimetres per year (Whillans, 1973(Whillans, , 1977Hughes, 1973;Thomas, 1976) . There is poor agreement between the various estimates of thinning-rate because of lack of information on the behavior of deep ice, and errors are difficult to assess since the result is rather sensitive to errors in the strain-rate measured perpendicular to the flow direction.…”
Section: The Stability Of the West Antarctic Ice Sheetmentioning
confidence: 99%
“…RonnelFilchner and Ross ice shelves especially, probably play a significant role in influencing the evolution of the West Antarctic Ice Sheet (WAIS) whose base is mostly below sea level and so may be vulnerable to small changes in thickness around itsmargin (e.g. Hughes 1973, Mercer 1978,ThomasetaL 1979. TheAntarctic Peninsula Ice Sheet is somewhat different from the rest of WAIS, in that it covers a mountainous terrain with the bedrock mostly well above sea level.…”
Section: Introductionmentioning
confidence: 99%